Tempol effect on epithelial-mesenchymal transition induced by hyperglycemia - Mohammad Jafari; Farahnaz Dadras; Hamid Reza Ghadimipour; Mohamad Ali Seif Rabiei; Farhad Khoshjou (Journal of Nephropathology, 2017)
Background: One of common mechanisms in pathophysiology of chronic kidney diseases is epithelial-mesenchymal transition (EMT). On the other hand oxidative stress has been known to participate in kidney damage of diabetic nephropathy (DN). Objectives: We studied if tempol, a well-known antioxidant agent, can ameliorate EMT in DN induced in male rats. Materials and Methods: Twenty-seven male rats were equally divided in to 4 groups. Group I (control or C), group II (diabetic or D), group III (T) rats which was given tempol (100 mg/kg/day) by gavages for 28 days and group IV (D&T) was diabetic rats that also received same dose of tempol. After treatment, their kidneys were studied by immunohistochemicalstaining. Results: Pathological changes in the kidney were detected concurrently with increasing kidney weight and urinary albumin excretion. In addition, EMT indices, i.e. decline of E-cadherin and increase of α SMA staining were significantly emerged in the renal tubular cells of diabetic group and were partially modified in diabetic group which were simultaneously treated by tempol. Conclusions: Tempol can modify, but not significantly, EMT induced by DN.